MATHEMATICAL REASONING ABILITIES OF STUDENTS IN TERMS OF FIELD DEPENDENCE (FD) COGNITIVE STYLE IN PROBLEM-SOLVING - Zaini, Zaini (Multica Science and Technology, 2021)
Every individual has different abilities in translating problems because it is influenced by basic knowledge, experience, and cognitive. The cognitive types of FD were identical slower than others. This study describes the mathematical reasoning of students with cognitive type of FD in problem solving. The research data needed is the GEFT test, problem-solving tests, and interviews involving twostudents in level IV . All data were analyzed inductively. The results showed that students with the cognitive type of FD needed a long time to create connection to the problem thinking and they needed direction as a stimulus to stimulate their thinking. Lecturers can use realistic examples in the environment around them to make connections in their thinking.